2006
DOI: 10.1074/jbc.m603193200
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Testosterone Induces Apoptosis in Neuronal Cells

Abstract: Testosterone plays a crucial role in neuronal function, but elevated concentrations can have deleterious effects. Here we show that supraphysiological levels of testosterone (micromolar range) initiate the apoptotic cascade. We used three criteria, annexin V labeling, caspase activity, and DNA fragmentation, to determine that apoptotic pathways were activated by testosterone. Micromolar, but not nanomolar, testosterone concentrations increased the response in all three assays of apoptosis. signals lead to apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 68 publications
6
99
1
2
Order By: Relevance
“…The receptor mediating these protective effects is thought to be AR due to the fact that AR antagonists block the neuroprotective effects [163; 164]. In contrast, supraphysiological levels of T have been found to increase neuronal apoptosis [165]. In fact, the damage-promoting effects of T have been observed in several experimental models.…”
Section: Neuroprotective Verses Neuroendangering -Genomic Verses Nongmentioning
confidence: 99%
“…The receptor mediating these protective effects is thought to be AR due to the fact that AR antagonists block the neuroprotective effects [163; 164]. In contrast, supraphysiological levels of T have been found to increase neuronal apoptosis [165]. In fact, the damage-promoting effects of T have been observed in several experimental models.…”
Section: Neuroprotective Verses Neuroendangering -Genomic Verses Nongmentioning
confidence: 99%
“…Studies have demonstrated AAS to be neurotoxic when injected in the proximity of peripheral nerves [27]. Although the exact mechanism by which this occurs is poorly understood, it is postulated that AAS initiate the apoptotic cascade of neuronal cells [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Long-term administration of nandrolone decanoate results in increased activation of caspase-3 and apoptosis throughout hippocampal and cortical structures [79]. Several in vitro studies have also demonstrated that exposure of neuroblastoma cells, primary hippocampal cells, and pheochromocytoma cells to AS can result in increased activation of caspase-3 [15,80,81]. Caspase-3 can be activated in both extrinsic and intrinsic apoptosis pathways and exerts a pivotal role in the execution of the apoptotic process by proteolytic cleavage of several proteins and chromatin condensation, resulting in DNA fragmentation and other changes throughout the apoptotic process.…”
Section: Pathophysiological Mechanisms Associated To As-induced Neuromentioning
confidence: 99%
“…Interestingly, in neuroblastoma cell culture, exposure to testosterone-induced concentrationdependent sustained increase in intracellular calcium concentration that involved up-regulation of inositol-triphosphate receptor (InsP 3 R) type I-induced calcium release [15]. As demonstrated elsewhere, prolonged calcium overload can trigger apoptosis in several cell types [83].…”
Section: Pathophysiological Mechanisms Associated To As-induced Neuromentioning
confidence: 99%
See 1 more Smart Citation